Pengembangan Media Patunglahan untuk Pembelajaran Matematika pada Siswa Kelas I SD Negeri Ketangi - Angger Aulia Artha; Rintis Rizkia Pangestika; Titi Anjarini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Mathematics instruction in the lower grades of elementary school requires learning media capable of transforming abstract concepts into concrete learning experiences. Preliminary observations at SD Negeri Ketangi revealed that the teaching of addition was dominated by lecture methods and simple visual aids, resulting in low student engagement and limited conceptual understanding. This study aimed to develop the "Patunglahan" learning medium for teaching addition and to determine its feasibility. The study employed the ADDIE Research and Development (R&D) model, comprising the stages of Analysis, Design, Development, Implementation, and Evaluation. The results indicated that the medium achieved a validity rating of 75% from media experts and 73% from subject matter experts, both of which were deemed valid. Student response reached 100%, indicating high practicality, while the level of instructional implementation also reached 100%. Effectiveness testing yielded N-Gain scores of 0.63 in the limited trial and 0.90 in the large-scale trial, both indicating high effectiveness. Thus, the "Patunglahan" learning medium is considered valid, practical, and effective for teaching addition to first-grade elementary school students.